PENGARUH METODE THINK PHARE AND SHARE DENGAN ALAT PERMAINAN EDUKATIF ULAR TANGGA TERHADAP MOTIVASI BELAJAR ANAK SEKOLAH DASAR (SD) - KEVIN WILLIAM ANDRI SIAHAAN; JANRES SINAGA; MIRANDA SIMANJUNTAK (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
Games as tools in education is one of the media-based simulation designed to stimulate the existing problems, in order to obtain the essence of science that can be used to solve the problem. This research was conducted with the aim of increasing the learning motivation of elementary school (SD) children by utilizing educational games. The results of this study are expected to provide an alternative activity to play in learning process and cultivate children to skillfully handle the problem independently, encouraging teachers to be more creative in educating the children with media interest and in accordance with the children's development. This study used a quasi-experimental design. The data collection technique used was the test and observation guidelines. Implementation of research had been done in class III SD Plus Tigabalata Simalungun district. The research result showed that the activity of students in the learning was 84 which is very active. The result of learning process skills was 81, while learning completeness score was 88. The test results influenced the activity of the students’ learning motivation as big as 0,684. There was still 0,352 of variance which was influenced by other variables. The influence of skills in the learning process of students to the students test scores was 0,616. It means, there are other variables which influence the test scores as big as 0,384. Comparative tests between pretest and post-test (t test) was t = 12,2*, means that there was motivation to learn outcomes before and after implementation.